Context-Dependent Drivers of Discretionary Debt Decisions: Explaining Willingness to Borrow for Experiential Purchases - Tully, Stephanie M; Sharma, Eesha (Journal of Consumer Research, 2018)
Abstract Mental accounting research suggests that consumers prefer borrowing for longer-lasting purchases in order to receive benefits from the purchases as they pay for them. In contrast, two sets of archival data and five lab studies show that consumers are more willing to borrow for experiential versus material purchases, even though experiential purchases tend to have a shorter physical duration. Further, framing the same purchase as more experiential than material increases willingness to borrow. This effect occurs because purchase timing is more important for experiential purchases—a function of consumers’ aversion to missing out on planned consumption. Thus, we moderate the proposed effect by varying whether the borrowing decision impacts planned consumption. Other differences between material and experiential purchases, such as scarcity or expected happiness, cannot similarly explain our results. Moreover, our conceptualization allows us to reconcile the apparent contradiction between the previous and current research by examining the relative impact of purchase-timing importance and payment-benefit duration matching in different contexts (i.e., “purchasing” and “source-of-funding” decisions).